Contaminant spreading by natural convection in a box - Tran, Tran Van; Thang, Nguyen Ngoc; Thuy, Nguyen Thi (Vietnam Journal of Mechanics, 2016)
In this paper the spreading of a contaminant accompanied  with natural convection in a box is numerically simulated. The box may be  considered as a cooking room or a working place where some sources of heat  and contaminant are in the simultaneous action. The box floor is supposed to  be divided into several domains with different boundary conditions for  temperature or heat flux. Here the purpose of the simulation is to  understand the contaminant spreading process in the box under the influence  of a convective motion. The model can be also applied for an enclosure with  separated parts differentially heated by the sunlight on its boundaries. A  good knowledge of this process is very useful for setting an efficient  ventilation scheme. In this paper the finite difference method based on the  Samarski scheme with ADI technique is applied for numerical simulation. Here  the box floor is divided into two domains of equal sizes but with different  temperature or heat flux. The contaminant source locates in the middle of  the box bottom. The simulation shows that over the part of the floor where  temperature or heat flux is greater the contaminant concentration is lager.  That result is in the accordance with the experiment done in the framework  of this~investigation.